Tinjauan Yuridis Terhadap Perjanjian Kerja Karyawan Kontrak Dengan Pt Tyfountex Indonesia Berdasarkan Undang-Undang Ketenagakerjaan - Novitasari, Pinaka Arum, Shalman Al Farizi, S.H., M.Kn (2016)
The employment agreement may be made orally or in writing. Normatively written form guaranteeing the rights and obligations of the parties, so that in case of controversies will greatly assist the process of evidence. But there is no doubt there are still many companies that do not or have not made a written employment agreement due to the lack of capable human resources and also because of the prevalence of belief on the basis of agreements made orally. Particular time work agreement made between PT Tyfountex Indonesia with a workforce of nature writing means certain time employment agreement that had existed since the bond agree on a specific time means employment agreement was made jointly between the company and the workforce thus the presence of an agreement is the validity of a contract.